Case Study Analysis Of Business Improvement Strategies In Talent Provision And Placement By ‘Banyak Jalan’ Management In Meeting, Convention, Exhibition Events In Jakarta - Fanny Heng; Vishnuvardhana S. Soeprapto (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
The MICE (Meeting, Incentive, Convention, Exhibition) industry in Jakarta has seen rapid growth, driving the demand for professional event. 'Banyak Jalan' Management emerged as a talent provider—offering SPGs, ushers, MCs, and more—focused on talent management strategies to enhance business competitiveness. This study aims to analyze the company’s strategies in talent provision and placement within the MICE sector. This research employs a qualitative case study approach. Data were collected through in-depth interviews with the company’s management (owner, HR, and finance), along with direct observation of several MICE events in Jakarta. The analysis focuses on recruitment, training, talent placement strategies, and strategic partnerships used to meet market demands. Findings indicate that strategies such as digital recruitment, tailored training, and service flexibility beyond standard operations contribute to business success. Long-term collaborations with major brands also strengthen stability. Challenges include demand fluctuations, limited availability of high-quality new talent, and expectation gaps with clients. It is recommended that the company develop an integrated digital platform, enhance talent evaluation systems, and expand strategic partnerships to support sustainable business growth.